Effects of Acute Exercise Duration on the Inhibition Aspect of Executive Function in Late Middle-Aged Adults - Chang, Yu-Kai; Chen, Feng-Tzu; Kuan, Garry; Wei, Gao-Xia; Chu, Chien-Heng; Yan, Jun; Chen, Ai-Guo; Hung, Tsung-Min (Frontiers in Aging Neuroscience, 2019)
Objective: This study investigated whether acute exercise duration affects inhibition in late middle-aged adults. Methods: Over four separate days, 40 late middle-aged adults completed, in a counterbalanced order, three exercise sessions consisting of single bouts of moderate-to-vigorous intensity cycling, with the main acute exercise durations being 10, 20, and 45 minutes, and a control session consisting of 30 minutes of reading. Their inhibition performance was then evaluated by administration of the Stroop test following each session. Results: The participants had shorter mean response times for both the congruent and neutral conditions of the Stroop following the acute exercise lasting 20 minutes than they did after the control session. The acute exercise lasting 20 minutes also resulted in shorter response times for both conditions of the Stroop than the acute exercise lasting only 10 minutes. Meanwhile, the acute exercise lasting 45 minutes resulted in a shorter mean response time for the neutral Stroop condition than did the control session. Finally, the acute exercise lasting 20 minutes resulted in the shortest mean response time of all four sessions for the Stroop incongruent condition. Conclusions: The above findings suggest that the moderate-to-vigorous intensity acute exercise lasting 20 minutes facilitated multiple cognitive function domains in general, whereas the exercise sessions of shorter and longer duration had negligible effects on executive function in the late middle-aged adults. These results highlight the need to consider the duration of any moderate-to-vigorous intensity exercise when developing acute exercise programs to facilitate executive function in aged populations.